Peran Moderasi Pengendalian Internal Untuk Audit Operasional Dalam Mempengaruhi Kinerja Karyawan - Wimba Respatia (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2022)
This study aims to prove empirically: (1) the effect of operational audit on employee performance, and (2) the moderating role of internal control in influecing operational audit to employee performance. The research was conducted at BKM Surabaya City. data obtained through a questionnaire. 39 questionnaires that can be analyzed. Data analysis techniques used: response bias test, descriptive statistics, classical assumption test and multiple regression analysis. research findings include: (1) Operational audit has a positive effect on employee performance, (2) internal control positive effect on employee performance, and (3) internal control weakens operational audit influence on employee performance.